Assembled Nanostructured Architectures Studied By Grazing Incidence X-Ray Scattering - Davide Altamura; Teresa Sibillano; Dritan Siliqi; Liberato De Caro; Cinzia Giannini (Nanomaterials and Nanotechnology)
In this chapter, we will focus on a specific X‐raybased technique among those employed in surface science and which is especially suitable for the study of self‐assembled nanocrystals: Grazing Incidence Small Angle X‐ray Scattering (GISAXS). We will first introduce the main field of investigation considered herein, with basic notions of X‐ray scattering from surfaces, and then address basic concepts about GISAXS. Finally, we will describe a few relevant examples of studies, of nanostructured architectures, through ex situ and in situ experiments of grazing incidence X‐ray scattering. This manuscript is focused on the former, showing that they can be performed by using laboratory instruments. In situ investigations still need synchrotron radiation sources in most cases; therefore, only a few examples selected from the literature are reported here, for the sake of completeness. The experiments described are mainly performed in the small angle range, providing information on the size and shape of nanocrystals, together with their spatial arrangement. Both 2D and 3D architectures are considered. In particular, GISAXS measurements of 2D superlattices of nano‐octapods, performed both at a third generation synchrotron beamline and with a table‐top set‐up, are compared; the employed table‐top set‐up is described in a dedicated paragraph. Further examples of grazing incidence studies as performed by the authors with a table‐top set‐up are reported: a GISAXS study of 3D iron oxide nanocrystal superlattices, showing the importance of modelling in order to obtain structural information from data; a combined small/wide angle scattering (GISAXS/GIWAXS) study of 3D PbS nanocrystal superlattices; and a GIWAXS study of P3HT nanofibres, showing how the ordering at the molecular and atomic length scales can be obtained by exploring different angular ranges in the same grazing incidence geometry. Finally, selected examples of in situ GISAXS studies, performed with synchrotron radiation sources, are described.